Interrelationships Among Sperm Quality Parameters, Cryocapacitation Status, Oxidative Markers and CASA Traits of Fresh and Frozen-thawed Semen of Gir and Murrah Bulls - Chaturvedi, Devangana; Dhami, Arjun J.; Chaudhari, Dinesh V. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This investigation was carried out on three breeding bulls each of Gir and Murrah breeds to evaluate the interrelationships among  sperm quality attributes, cryo-capacitation, oxidative markers and Biovis CASA traits of fresh and frozen thawed semen. The ejaculates  (n=4/bull) having >75% initial motility were split-diluted @ 100 million sperm/mL in TFYG extender without (control) and with fortification  of Mifepristone, Sericin and Taurine, filled in French mini straws, and were frozen using a programmable biofreezer. The straws were  thawed in water bath at 37°C for 30 sec. The freshly diluted and frozen-thawed samples were assessed for various routine sperm quality  parameters, cryo-capacitation status by CTC fluorescence, oxidative markers and for various motion characteristics/kinematics by Biovis  CASA, the overall means of which are tabulated. The Pearson’s correlations studied among all these traits in freshly diluted and frozen thawed semen of both the species revealed that the sperm motility, HOS reactive sperm, live sperm and non-capacitated sperm were  significantly (p
Keywords: Bovine semen; Frozen-thawed sperm; Interrelationships; Kinematics; Oxidative markers; Sperm quality